Maruja Mallo-Alfonso Reyes collected letters (1938-1945). Annotated edition - Pérez Rodríguez, Mª Antonia (Madrygal. Revista de Estudios Gallegos, 2014)
Collected letters between Maruja Mallo and Alfonso Reyes trascend privacy, henceforth, this annotated edition’s attempt is to contribute not only to the design of a Hispanic literary system map that has considered both socio-economic aspects and historical circumstances, but also to realize the value of correspondence as an information source. In addition, it tries to make the role played by Spanish Civil War refugees visible, particularly through publications. It also tries to visualize those cultural links created with Mexico and Argentina in the period 1938-1945. Notes are not for bibliography or people mentioned in the letters, but for the context itself and for some of the socio-personal and professional relationships of the writer, painter and exiled friends in the above mentioned countries.